A Regionwise Comparative Study Of Post Punch Graft Appearance Of Repigmentation (AOR) Time In Cutaneous Achromia - Lahiri Koushik; Sengupta Sujit Ranjan (Wolters Kluwer Medknow Publications, 1998)
This study included 110 cases of stable and refractory depigmented skin conditions, of which 67 were female and 43 male. Age ranged between 6 and 71 years. A total of 1742 grafts were placed over 177 lesions on 29 regions and the cases were followed up to a maximum period of 2 years. The appearance of repigmentation (AOR) time was noted in different regions of the body. It was observed that exposed parts exhibit better outcome in comparison to covered and shadowed part. AOR ranged between 14 and 39 days, with an overall average being approximately 21.6 days.